The use of selenium in the sheep industry: A review - Ortunho, Vanessa Veronese; Beline, Mariane [UNESP]; Souza Carli, Maria Eduarda de; Peres Carvalho, Gabriela de Souza [UNESP] (Univ Federal Ceara, Centro Ciencias Agrarias, 2016)
The importance of mineral supplementation in cattle is already proven and its benefits are widely known, but in the sheep industry this topic is incipient and research are scarce. This article made a literature review addressing the Selenium functions and their use in the sheep industry. It was noticed that the mineral is essential to increase the reproductive rates of the species and therefore stimulates that experiments are conducted to verify the best ways of supplementation and doses to be used.
Keywords: minerals; reproduction; sheep